2016
DOI: 10.1371/journal.pone.0152103
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Host Shifts of Cotton-Melon Aphids in Northern China

Abstract: Aphis gossypii Glover (Hemiptera: Aphididae) is a serious pest of cotton in northern China. A microsatellite analysis was used to characterize the genetic structure of A. gossypii populations from different geographic, host plant, and seasonal populations in 2014. Among 906 individuals, 507 multilocus genotypes were identified, with genotypic richness values of 0.07–1.00 for the populations. We observed moderate levels of genetic differentiation among geographic populations (FST = 0.103; 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Many studies have reported the existence of host-specific A. gossypii biotypes, but a lack of standardization has prevented comparisons of biotypes (Ebert and Cartwright 1997). In a previous study using SSR markers, we found that A. gossypii populations in northern China exhibited greater genotypic diversity, and the 31 populations in northern China could be classified into one of 3 biotypes according to host species (Luo et al 2016). Unlike in other places, the microsatellite loci had high diversity in northern China, making it difficult to practically use.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Many studies have reported the existence of host-specific A. gossypii biotypes, but a lack of standardization has prevented comparisons of biotypes (Ebert and Cartwright 1997). In a previous study using SSR markers, we found that A. gossypii populations in northern China exhibited greater genotypic diversity, and the 31 populations in northern China could be classified into one of 3 biotypes according to host species (Luo et al 2016). Unlike in other places, the microsatellite loci had high diversity in northern China, making it difficult to practically use.…”
Section: Discussionmentioning
confidence: 96%
“…Bioassay of laboratory host-transfer experiments was the original method used to confirm A. gossypii biotypes (Guldemond et al 1994;Liu et al 2008;Carletto et al 2009b;Wang et al 2016). Simple sequence repeat (SSR) markers were another popular method to assess A. gossypii diversity (Vanlerberghe-Masutti et al 1999;Thomas et al 2012;Luo et al 2016). Mitochondrial gene sequence polymorphisms were also used to distinguish A. gossypii biotypes (Carletto et al 2009a;Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations